CORRELATION BETWEEN CARDIOMETABOLIC FACTORS AND FUNCTIONAL DISORDERS OF THE SYMPATHOADRENAL SYSTEM IN YOUNG PATIENTS WITH NEWLY DIAGNOSED ANGINA PECTORIS AND PREDICTION OF ITS DEVELOPMENT (International journal of medical sciences, 2026)
Background: The incidence of early-onset coronary artery disease (CAD), manifesting as angina pectoris in young adults, is steadily rising. The interplay between cardiometabolic abnormalities and the sympathoadrenal system (SAS) is hypothesized to be a key driver of premature atherosclerosis and rapid disease progression. Objective: To investigate the correlation between cardiometabolic factors and functional disorders of the sympathoadrenal system in young patients with newly diagnosed angina pectoris, and to develop prognostic criteria for disease progression.